Factors influencing the perceptions of service delivery by local municipalities in the Central District Municipality in the North West / Pule Glenelg Mogapi - Mogapi, Pule Glenelg (2014)
The study revolves around factors influencing the perceptions of service delivery by local municipalities in the Central District Municipality in the North West Province. Service delivery in general, as perceived by communities, has been a serious dilemma for most South African local municipalities. Factors in service delivery, as applicable in service marketing, have been examined through a detailed SERVQUAL research method. The focus areas have been service quality dimensions: • Reliability : the ability to deliver the promised service dependably and accurately; • Responsiveness : willingness to help and provide prompt customer service; • Assurance : knowledge, courtesy and ability of service providers to inspire trust and confidence • Empathy : caring and individualised attention given to clients; and • Tangibles : appearance of physical facilities, equipments, personnel and written materials. All five local municipalities in the Central District were involved in the study, and the main findings indicate that the residents in all the affected municipalities do not have confidence in the local government for service delivery. All five municipalities performed badly on the aspect of reliability and there is negative perception on responsiveness and willingness to provide prompt service by all the municipalities. The municipalities are perceived not to be able to command respect and instil confidence on their residents. The performance on empathy, where individual customised services are expected is poor. It is only on tangibles, where physical facilities are regarded as satisfactory. It is recommended that all municipalities should look inwardly and improve on their capacity on skills, financial management as well as bench-marking with international cities and towns for effective municipal service delivery. Service marketing as a management principle should be implemented immediately to save the current situation of loss of clientele and customer confidence. Other areas of quality improvement to be looked at are Total Quality Management and Work Improvement Team Strategy. === (MBA) North-West University, Mafikeng Campus, 2006